Three review studies types in educational research: characterization and analysis - Ana Lucia Felix dos Santos; Elizabete Pereira Barbosa; Fernando Xavier Silva; Valdelaine da Rosa Mendes (Tópicos Educacionais)
This paper aims to analyse how three types of review studies (literature review, systematic review, and bibliometric studies) are approached in researches on educational knowledge production. Here, review studies are understood as those dedicated to mapping the production of knowledge, seeking to problematize trends and challenges, but also seeking to signal new demands from a given academic area and the methodological research lines. The methodology involved selecting 12 papers (3 literature reviews, 4 systematic reviews and 5 bibliometric studies). Initially, the text draws a panorama of review studies, it subsequently presents the 12 review papers, pointing out the main approximations, dissonances, trends and gaps, signalling new directions for studies and research on review studies. It was observed the works can weave disparate methodological procedures, but still contribute to the elaboration of important syntheses for the researches in the educational field.